Uranium Decontamination from Waste Soils by Chlorination with ZrCl4 in LiCl-KCl Eutectic Salt - Jang, Junhyuk; Kim, Tack-Jin; Park, Sungbin (Science and technology of nuclear installations, 2021)
The dissolution behavior of U, contained in the soils, was examined through chlorination with ZrCl4 to reduce the U concentration to clearance levels. Natural soils, composed of Si, Al, and approximately 2 ppm U, acted as surrogates for the contaminated soils. A salt mixture of LiCl-KCl-ZrCl4 was prepared in an Al2O3 crucible at 500°C, and SiO2 or natural soils were loaded for the chemical reactions. The reaction of SiO2 and Al2O3 with ZrCl4 was monitored by cyclic voltammetry, and no obvious change was observed. The results showed that SiO2 and Al2O3 were stable against ZrCl4. The reaction of natural soils with ZrCl4 indicated that the U content decreased from 2 to 1.2 ppm, while ∼0.4 ppm U appeared in the salt. Thus, the U, in the soils, dissolved into the salt by chlorination with ZrCl4. Therefore, based on these results, a new method to remediate U-contaminated soil wastes by chlorination with ZrCl4, followed by electrorefining of U, is suggested.